Design development and fabrication of motorised tricycle for the disabled - 369760 Lim, Boon Han (Skudai : Universiti Teknologi Malaysia, 2003)
Project paper(Sarjana Muda Kejuruteraan Mekanikal) - Universiti Teknologi Malaysia, 2003